Perancangan Visual Branding UI/UX Website dan Logo E-Koperasi Sebagai Media Digital Layanan Koperasi Politeknik Negeri Batam - Fatma Nabila; Ayu Surani Triningsih; Muhammad Rahendra Try Putra Gagatan; Lea Stefanny Lawrence; Doni Jefrian; Farhan Satyaputra Faisal; Kawan Pandiangan; Miftahul Husna Ghawa (Politeknik Negeri Batam, 2026)
With the rapid development of digital technology, cooperatives are required to transform from conventional systems to digital-based services in order to improve efficiency and accessibility. This transformation encompasses not only service systems but also visual communication and brand identity. However, the E-Koperasi website of the Batam State Polytechnic does not yet have a specifically designed and consistent visual identity. This study aims to design a visual brand identity through the development of a logo and the UI/UX design of the E-Koperasi website, which is accessible via both desktop and mobile devices. The study employs a descriptive quantitative approach using the Design Thinking methodology, which includes the stages of empathize, define, ideate, prototype, and test. Data collection was conducted through observation, interviews, literature review, and questionnaires. Testing was performed using Expert Judgment and Usability Testing, while evaluation utilized Nielsen’s Attributes of Usability (NAU) method. The research resulted in a final logo and a responsive website UI/UX design. The evaluation using the NAU method on 100 respondents yielded an average (mean) score of 4,24, falling into the “Very Good” category. Based on these results, the visual branding and UI/UX design of the SOKA website are deemed to have met user needs as a digital platform for the services of the Batam State Polytechnic Cooperative.